FAKTOR-FAKTOR YANG MEMPENGARUHI WAKTU TUNGGU PELAYANAN DI INSTALASI RAWAT JALAN RSUD LUWUK BANGGAI PADA MASA PANDEMI COVID-19 TAHUN 2021 - Momen Amalia; Era Pratiwi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Waiting time is the time used by patients to get outpatient service from the place of registration to getting doctor medical check up. Patient waiting time is one component has the potential cause dissatifaction. Purpose of this study was to look at the factors affect waiting time for service in outpatient instaations during covid-19 pandemic RSUD Luwuk Banggai. This study used a quantitative method with a cross sectional study design. Data collection used a questionnare. Sampel in this study were patients in the outpatients installations RSUD Luwuk Banggai. Total of 85 people. Data analysis used chi-Square test Indicate registration administration has effecton waiting time for service in outpatient installation (p value 0,000 < 0,05). Facilities and infrastructure affect affect patient waiting time from registering to receiving doctor service for 64,82 minutes. Registration administration, human resources and infrastructure have an affect on patient waiting time and patient waiting time in outpatient instalation service not in accordinate with established standard be appointed because medical record still manual and doctor slow in conducting medical check up. Expected the hospital used medical records based on SMIRS and increase the number of doctors.